Regenerating human epithelia with cultured stem cells: feeder cells, organoids and beyond - Robert E Hynds; Paola Bonfanti; Sam M Janes (EMBO Molecular Medicine)
Abstract More than 40 years ago, Howard Green's laboratory developed a method for long‐term expansion of primary human epidermal keratinocytes by co‐culture with 3T3 mouse embryonic fibroblasts. This was a breakthrough for in vitro cultivation of cells from human skin and later for other epithelia: it led to the first stem cell therapy using cultured cells and has vastly increased our understanding of epithelial stem cell biology. In recent years, new methods to expand epithelial cells as three‐dimensional organoids have provided novel means to investigate the functions of these cells in health and disease. Here, we outline the history of stratified epithelial stem cell culture and the application of cultured epithelial cells in clinical therapies. We further discuss the derivation of organoids from other types of epithelia and the challenges that remain for the translation of novel stem cell therapies toward clinical use.